Tracing The Glory of Sri-Vijayan Empire Art Style in Southeast Asia - Andre Syafrony (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2022)
The link between civilizations influenced by Indian culture in Indonesia and Thailand has been thought-provoking. Many discoveries are mainly found in southern Thailand, which is similar to Javanese 9th-century artwork. This proves that the constituencies in South-East Asia had been in contact with each other in the past. Therefore, this paper aims to explore the concept of cultural influence and link it with the influence of Indian culture in South-East Asia, leading to the cultural conceptualization of the art style during the particular period of the Srivijaya Empire. Hubungan antara peradaban yang dipengaruhi oleh budaya India di Indonesia dan Thailand telah lama menimbulkan kekaguman. Banyak penemuan di Thailand selatan, seperti karya seni Jawa abad ke-9. Ini membuktikan bahwa daerah-daerah kekuasaan di Asia Tenggara telah saling bertukar kebudayaan di masa lalu. Oleh karena itu, tulisan ini bertujuan untuk mengeksplorasi pengaruh budaya dan menghubungkannya dengan pengaruh budaya India di Asia Tenggara, yang mengarah pada konseptualisasi budaya gaya seni pada masa Kerajaan Sriwijaya dengan menggunakan analisis sastra dan dokumen